Analisis Penerapan Undang-Undang Nomor 1 Tahun 2023 Tentang KUHP Terhadap Batas Minimal Usia Perkawinan - Masayu Robianti; Fathur Rachman; Andriansyah Kartadinata (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
This study aims to analyze the reasons for the legislators to change the setting of the minimum age for marriage for women according to the Law of the Republic of Indonesia Number 1 of 2023 concerning the Criminal Code Amendment to Law Number 16 of 2019 concerning Marriage. The choice of this theme is based on the constitutional background in the previous Marriage Law, the contents of Article - Marriage Law Number 16 of 2019 are not in line with the law that was born later, namely Law 35 of 2014 concerning Amendments to Law Number 23 of 2002 on Child Protection. Based on the above, this paper raises the formulation of the problem: what are the reasons for the legislators to change the minimum marriage limit based on the Law of the Republic of Indonesia Number 1 of 2023 concerning the Criminal Code for Amendments to the Marriage Law. This research is a normative juridical research, using historical approach (historical approach) and statutory approach (statue approach). and the statutory approach. Primary, secondary and tertiary legal materials obtained by the author were analyzed. The results of this study the reasons for the legislators to change the minimum marriage limit for women based on the Law of the Republic of Indonesia Number 1 of 2023 concerning the Criminal Code Amendment to Law Number 16 of 2019 concerning Marriage is the result of this research. Philosophically, this is to eliminate discrimination in the acquisition of basic rights and constitutional rights arising from differences in the minimum age limit for marriage as stipulated in Law no. 16 of 2019. Sociologically, this is to prevent the occurrence of early marriage which will have a further impact on the occurrence of pregnant women and childbirth at an early age which are at high risk for the health of the mother and baby. Juridically, this is a fulfillment of the mandate of the Constitutional Court Decision No. 22/PUU-XV/2017 related to the unification of the minimum age for marriage between men and women, synchronizing the law alongside the Child Protection Act, and part of ensuring the ability to act within the law.